STUDENTS’ READING PREFERENCE AND ITS IMPLICATIONS: A STUDY OF THREE ENGLISH EDUCATION DEPARTMENTS IN JEMBER - Sari Dewi, Noviyanti (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the students’ reading preference and its implications of three English Education Departments in Jember. Getting learners’ full attention in the learning process is very important, because the ability to read is one element of language competences that always needs to be elevated. However, reading material usually becomes the biggest obstacle for the lecturer to engage students’ full interest to the course. This study involved 273 students of three English Education Departments in Jember as research objects. Survey and interview methods were used to obtain the data. The research findings show that English Education Department students mostly interested to reading materials about entertainment and lifestyle, arts, religious, education and historical theme, and they avoid reading political and sport. Based on these findings, the suggestion for lecturers who specialize in the subjects related to reading activities is they should be able to present the teaching materials with themes favored by students in order to improve students’ reading motivation.